THE EMPOWERMENT OF VILLAGE HEALTH FORUM (VHF) IN ALERTED VILLAGE DEVELOPMENT - Didik G. Suharto; Kristina Setyowati (Spirit Publik: Jurnal Administrasi Publik, 2016)
The problem the partner (Village Health Forum/VHF) encountered in developing alerted village could be approached from managerial capacity aspect and from the aspect of technical understanding capacity of members’ health. Considering the activity of service conducted, it could be explained that the activity focused on improving the members’ capacity in managing the institutionalism of VHF (particularly activity management, infrastructure and operating fund); and how the basic health knowledge capacity of VHF members as initiator, facilitator, and motivator supported the public health promotion. The activity of service to public in partner institution included: need assessment, institution capacity development, partnership development, and monitoring and evaluation. The factors affecting the program’s smoothness and success were: the factor deriving from VHF administrator/cadre, VHF institution, village government, Health Office/Public Health Center, private sector/company, and society.Keywords: empowerment; Village Health Forum, alerted village